Synthesisation of zinc oxide nanowires via hybrid microwave assisted sonochemical technique at various microwave power / Maryam Mohammad … [et al] - Mohammad, Maryam; Malek, Mohd Firdaus; Abd Halim, Muhammad Faizal; Mohammad Zamri, Nurul Zulaikha; Bakri, Mohamad Dzulfiqar; Khusaimi, Zuraida; Mamat, Mohamad Hafiz; Mahmood, Mohamad Rusop; Tetsuo, Soga (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Zinc oxide nanowires (ZnO NWs) have been successfully synthesized via a hybrid microwave-assisted sonochemical technique (HMAST) using zinc acetate dehydrate as starting material. The optimized parameters were set at 12.5 mM solution concentration and a rapid deposition time of 60 minutes. The microwave power was varied from 100 to 800 Watts and the effect of microwave power on the morphological, structural, and optical properties of the ZnO NWs has also been studied. Results showed an aligned, uniformly distributed hexagonal wurtzite structure of ZnO NWs was produced, which were augmented at 600 W microwave power, having the smallest diameter size of 29.66 nm. The XRD graph showed that the ZnO NWs produced are highly crystalline, exhibiting the sharpest and narrowest intensity of (002) peaks and a crystallite size of 18.60 nm. The transmittance spectra obtained by UV-Vis would be 89.72%, having a sharp absorption edge, implying the lower particle size of ZnO as well as exhibiting high absorbance in the ultraviolet region, indicating good crystallinity. From the findings, it can be confirmed that the microwave-assisted method helped in improving the formation of higher quality ZnO NWs that can be befittingly applied in many devices such as photocatalysts and sensors due to their excellent electrochemical properties.